2022
DOI: 10.1186/s12913-022-08804-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for publicly reported quality indicators in residential long-term care: a systematic review

Abstract: Background An increasing number of countries are using or planning to use quality indicators (QIs) in residential long-term care. Knowledge regarding the current state of evidence on usage and methodological soundness of publicly reported clinical indicators of quality in nursing homes is needed. The study aimed to answer the questions: 1) Which health-related QIs for residents in long-term care are currently publicly reported internationally? and 2) What is the methodological quality of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Two items were poorly scored: evidence supporting the KPIs and the lack of piloting and post-development evaluation. Our findings align with previous analyses in areas such as school feeding programs [ 23 ], long-term care [ 26 ], or dental care [ 24 ]. Higher scores in domain #1 (Purpose, relevance, and context) suggest that KPI developers have a clear vision of their objectives.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two items were poorly scored: evidence supporting the KPIs and the lack of piloting and post-development evaluation. Our findings align with previous analyses in areas such as school feeding programs [ 23 ], long-term care [ 26 ], or dental care [ 24 ]. Higher scores in domain #1 (Purpose, relevance, and context) suggest that KPI developers have a clear vision of their objectives.…”
Section: Discussionsupporting
confidence: 90%
“…AIRE, a validated instrument designed for indicator quality assessment [ 21 ], was initially derived from the AGREE (Appraisal of Guidelines Through Research and Evaluation) instrument [ 22 ]. Utilized in several systematic reviews on indicator quality [ 23 26 ], the AIRE instrument comprises 20 items across four domains: "Purpose, relevance, and organizational context," "Stakeholder involvement," "Scientific evidence," and "Additional evidence, formulation, and usage." Each item presents a statement about the quality of the indicator and is scored on a 4-point scale (1 ‘totally disagree or no information provided’ to 4 ‘strongly agree’).…”
Section: Methodsmentioning
confidence: 99%
“…Other reviews also revealed poor reporting of the methods used for developing quality indicators that complicated the assessment of the methodological rigor and quality of the studies. 57 , 58 , 59 It is important to highlight that there was no disparity in quality assessment between studies that developed a set of KPIs solely for clinical services compared to those that incorporated support activities.…”
Section: Discussionmentioning
confidence: 99%
“…(2021) that analyze the development of quality indicators for dementia care. A recent systematic review (Osińska et al, 2022) analyzed the quality indicators in residential long-term care, specifically those employed for public reporting.…”
mentioning
confidence: 99%